Toward a detoxification fabric against nerve gas agents: guanidine-functionalized poly[2-(3-butenyl)-2-oxazoline]/Nylon-6, 6 nanofibers. Issue 25 (7th March 2017) - Ying, Wu Bin; Kim, Sohee; Lee, Min Woo; Go, Na Yeong; Jung, Hyunsook; Ryu, Sam Gon; Lee, Bumjae; Lee, Kyung Jin
Abstract : A novel guanidine-functionalized polymer, poly[2-(3-butenyl)-2-oxazoline] (PBuOxz), has been co-electrospun with Nylon-6, 6 to form fibers that could be used for the decontamination of chemical warfare agents (CWAs). Abstract : A novel guanidine-functionalized polymer, poly[2-(3-butenyl)-2-oxazoline] (PBuOxz), has been co-electrospun with Nylon-6, 6 to form fibers that could be used for the decontamination of chemical warfare agents (CWAs). PBuOxz was obtained from the living cationic polymerization of 2-(3-butenyl)-2-oxazoline, which was synthesized starting from 4-pentenoic acid. This clickable PBuOxz polymer could be easily functionalized through the introduction of amine groups via thiol–ene click chemistry, followed by guanidinylation to form guanidine-functionalized PBuOxz (G-PBuOxz). The synthesized G-PBuOxz/Nylon-6, 6 fibers are an active hydrolysis species for diisopropyl fluorophosphate (DFP), an organophosphate mimic of nerve agents. The decontamination efficiency for DFP could be as high as 100% under trace aqueous solution conditions using this G-PBuOxz/Nylon-6, 6 fiber as the decontamination agent at the ratio of [guanidine]/[DFP] = 100/1 in 2 hours. The hydrolysis occurs via a general SN 2 mechanism for this G-PBuOxz-based catalysis. Furthermore, the kinetics of decontamination were also investigated based on time and guanidine concentration. Hence, this G-PBuOxz/Nylon-6, 6 fiber is effective as a hydrolyzing agent against toxic organophosphates, and thus exhibits potential as a material for protecting against chemical warfare agents.